Behavior and evolution of birds readings from Scientific American magazine - Mock, Douglas W. (W.H. Freeman, 1991)
Featuring 12 articles drawn from "Scientific American", this collection reflects the contribution of studies in behaviour and ecology to our understanding of birds. The collection also indicates how important new techniques from such disciplines as molecular biology and neurobiology have been applied to longstanding ornithological questions. Birds have often been the subject of studies leading to far-reaching theories in animal behaviour - particularly in the areas of sexual selection, inclusive fitness, and optimal foraging.